Transformasi Energi Terbarukan dalam Kerangka Pembangunan Berkelanjutan: Studi Evaluatif Atas Kebijakan dan Implementasi di Indonesia - Muhayatul, Muhayatul; Umar, Genius (PT Hakhara Akademia Indonesia, 2025)
Renewable energy transformation is one of the pillars of realizing sustainable development in Indonesia. This study aims to evaluate the Indonesian government's policies in supporting renewable energy transformation, assess the extent of its implementation at the national and regional levels, and identify the challenges and obstacles faced in the process. Through a qualitative descriptive approach, this study analyzes various policies and implementation in the field based on secondary data from journals, government reports, and scientific publications. The results of the study show that although Indonesia has had a strong commitment through various regulations, its implementation still faces various obstacles, especially related to funding, infrastructure readiness, and coordination between institutions. For this reason, a more integrative and collaborative strategy is needed between the central government, regional governments, the private sector, and the community so that the energy transition can take place more effectively and evenly. This study is expected to contribute to the formulation of energy policies that are more adaptive and responsive to the dynamics of sustainable development in Indonesia.